Optimising pain management - An update - Natalie Schellack; Ama S. Annor (South African Family Practice)
The key to optimal pain management is the ability to effectively monitor the patient to ensure pain relief, whilst minimising or managing the side-effects of pain medication. This will only be possible though the collaborative work of all healthcare professionals managing the patient. This article provides an overview of the requirements for optimising pharmacotherapeutic pain management.